Clinical and Histopathologic Characteristics of Oral and Maxillofacial Malignancies: A 5-year Assessment in an Iranian Population - Saber Babazadeh; Shadi Saghafi Khadem; Zeinab Mousavi (Journal of Mashhad Dental School)
Background: This study aimed to investigate the clinical and histopathological characteristics of oral and maxillofacial malignancies and their association with the 5-year survival rate of patients in an Iranian population.Methods and Materials: This cross-sectional study analyzed data from 99 patients diagnosed with an oral or maxillofacial malignancy. Patients had admitted to the Pathology Department of Mashhad Dental School from January 2015- January 2019 and their records were retrospectively reviewed. Patients were followed until 5 years after their initial diagnosis and their current status was documented. The patients’ demographic data were collected. The type of malignancy, based on the clinical and histopathologic diagnoses, was recorded. Patient mortality rate and survival time were also calculated. Statistical analysis was performed using Chi-square, Fisher's exact test and Mann-Whitney-U test. Survival analysis was conducted using the Kaplan-Meier method. P-value less than 0.05 was considered statistically significant.Results: A total of 99 records were reviewed. Gender distribution frequency consisted of 58 male and 41 female patients. Patients had a mean age of 56.8±17.16 years. A total of 48 (48.5%) of patients had died due to oral cancer. The most common malignancies were low-grade SCC (28.3%) and high-grade SCC (25.3%). The most common site of involvement was the tongue (31.3%). The mortality rate in high-grade SCC (68%) was higher than low-grade SCC (35.7%). There was a statistically significant correlation between the type of malignancy and mortality rate (P=0.039). The greatest and lowest median survival time was observed in patients with adenoid cystic carcinoma (60 months) and mucoepidermoid carcinoma (16.8 months), respectively. Conclusion: This study provides valuable information about the pattern of oral malignancies, factors related to prognosis, and survival rates in the studied population. The type of malignancy was the only significant factor associated with mortality.